Pharmacological and toxicological evaluation of two anti-asthmatic polyherbal formulations - SALEEM,UZMA (2020)
Abstract The study aim was to evaluate the toxic potential of two polyherbal formulation i.e. “ PH 1 & PH 2” and scientific validation of their anti-asthmatic use. Acute oral toxicity study as per OECD 425 TG was conducted. For validation of anti-asthmatic claim, in vivo assay named Ovalbumin (OVA)-induced murine method in Wistar rats was used. Eosinophils and IgE antibody were quantified post-administration of low and high doses of the formulations. No mortality was observed in acute toxicity study. Elevated levels of alkaline phosphatase and damaged liver structure indicating the hepatotoxicity were more pronounced in PH 2 treated rats. Congestion in kidney tissue and increased urea level were evident of the nephrotoxic nature of PH 2 in animals. Treatment with selected polyherbal products decreased the MDA level while increasing the SOD and GSH levels in lung tissue homogenates. The maximum decrease in IgE load (3.18 ± 0.08 IU/mL) was found in rats treated with 12 mg/kg dose of PH 1 followed by 100 mg/kg dose of PH 2 (3.44 ± 0.06 IU/mL). It was concluded that both polyherbal formulations had anti-asthmatic activities, however, PH 1 exhibited the liver and kidney toxicity and should be cautiously used.